Designing a Teacher Training Education Programme. How to say Goodbye to Bulling at School and the role of ICTs - Papadaki, Aggeliki; Karagianni, Eleni; Driga, Anna Maria (Eximia, 2023)
The aim of the particular article is to design a one-day program for a specific group of teacher-trainees. In the first part, there is a description of the training context, including trainees’ characteristics, the main goal of the program, its location, duration and the resources to be used. In the second part, there is a detailed analysis of the course, including the content, its objectives, the stages, the procedure and the materials to be used, while at the same time, there is a critical evaluation of it with relevance to literature. In the third part, there is a critical discussion of the choices and approaches mentioned in the previous parts. Finally, there is a conclusion including all the concepts discussed.